LC-MS/MS를 이용한 견과류 중 트리코테센계 곰팡이 독소 10종 동시분석법 개발 - 김단비; 박지수; 유미영; Kim, Dan-Bi; Park, Ji-Su; Yoo, Mi-Young (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2018)
This study presents a method validation for extraction and quantitative analysis of trichothecene mycotoxins in nuts based on quick, easy, cheap, effective, rugged, and safe (QuEChERS) approach for extraction and enhanced matrix removal (EMR)-lipid-disperive-SPE (d-SPE) cleanup method, with detection and quantification by high-performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) in positive- and negative-ion modes. Linearity, precision, and accuracy were validated for LC-MS/MS methods. Results obtained with LC-MS/MS were linear, with correlation coefficient ($R^2$) of 0.998. Limits of detection and quantification for mycotoxins were $0.41-3.57μg/kg$ and $1.23-10.82μg/kg$, respectively. Intra- and inter-day precisions (RSD, %) were 0.40-8.44% and 1.93-12.46%, respectively. Results indicated to be rapidly and accurately identifying trichothecene mycotoxins and may be used as a suitable safety management method for nuts and nuts related commodities. 견과류 중에 있는 트리코테센계 곰팡이독소 오염도를 조사하기 위하여 LC-MS/MS를 이용한 정확성과 신뢰성을 동시에 확보할 수 있는 분석방법을 개발하였다. 견과류 중 트리코테센계 곰팡이 독소는 QuEChERS 추출 및 EMR-Lipid-dSPE 정제과정을 통하여 분석에 사용되었다. 검량선 작성을 위하여 트리코테센계 곰팡이독소 10종에 대하여 $2.00{\sim}75.00μg/kg$의 범위로 혼합표준용액을 제조하여 실험하였으며, 상관계수는 모두 0.998 이상으로 높은 직선성을 나타내었다. 분석방법의 검출한계는 $0.41{\sim}3.57μg/kg$로 나타났으며, 정량한계는 $1.23{\sim}10.82μg/kg$로 나타났다. 또한 트리코테센계 곰팡이 독소 10종에 대하여 각각 저, 중, 고 3가지 농도로 처리하여 회수율 실험을 수행한 결과 81.84~96.87%로 나타났다. 확립된 분석법으로 견과류 중 땅콩을 대상으로 오염도를 조사한 결과 1종에서 deoxynivalenol이 검출되었다. 이러한 결과를 바탕으로 확립된 시험법은 견과류 중 트리코테센계 곰팡이 독소 분석에 적합함을 확인할 수 있었으며 견과류 중 트리코테센계 곰팡이 독소 검출 가능성을 확인한바 보다 다양한 종류의 견과류에 대한 모니터링 조사가 필요한 것으로 판단된다.